FAKTOR-FAKTOR PENYEBAB KREDIT MACET DAN PENYELESAIANNYA PADA KREDIT USAHA RAKYAT (KUR) PT BANK RAKYAT INDONESIA CABANG SAMARINDA 1 UNIT SUNGAI KUNJANG. - Lumungan, Jeane Lumungan (EKONOMIA, 2017)
On December 1, 1997 inaugurated the Bank Rakyat Indonesia Unit Sungai Kunjang . Bank Rakyat Indonesia Unit Sungai Kunjang is domiciled at Ir Sutami No. 10 (front SMP 10). The research objective to be achieved in this study are: 1. To identify and analyze the increase in non-performing loans (NPL) PT Bank Rakyat Indonesia Unit Sungai Kunjang in the cause credit problems. 2. To know and analyze the increase in Loan to Deposit Ratio (LDR)) PT Bank Rakyat Indonesia Unit Sungai Kunjang in the cause of problem loans. The result of the calculation of Non Performing Loan (NPL) at PT Bank Rakyat Indonesia Samarinda Cabang 1 Unit Sungai Kunjang showed unfavorable results, due to an increase in non-performing loans (NPL), which caused the number of delinquent loans and jammed increased. This conclusion can be derived from the figures (in percentage) shown in the calculation of the ratio of Non Performing Loan (NPL). From this analysis, the hypothesis of Non Performing Loan (NPL) is acceptable, although an increase of 12:41% from 2013, but not in excess of the standard non-performing loan (NPL) ratio of 5%.Â